Ionic supramolecular polymerization of water-soluble porphyrins: balancing ionic attraction and steric repulsion to govern stacking. Issue 47 (26th October 2022) - Kanzaki, Chisako; Yoneda, Hiroshi; Nomura, Shota; Maeda, Takato; Numata, Munenori
Abstract : Anionic water-soluble porphyrins undergo supramolecular polymerization through two independent pathways—slipped stacking mediated by ionic interactions and face-to-face stacking with the assistance of hydrogen bonding of amide NH units. Abstract : We have synthesized novel water-soluble anionic porphyrin monomers that undergo pH-regulated ionic supramolecular polymerization in aqueous media. By tuning the total charge of the monomer, we selectively produced two different supramolecular polymers: J- and H-stacked. The main driving force toward the J-aggregated supramolecular polymers was the ionic interactions between the sulfonate and protonated pyrrole groups, ultimately affording neutral supramolecular polymers. In these J-aggregated supramolecular polymers, amide groups were aligned regularly along polymer wedges, which further assembled in an edge-to-edge manner to afford nanosheets. In contrast, the H-aggregated supramolecular polymers remained anionic, with their amide NH moieties acting as anion receptors along the polymer chains, thereby minimizing repulsion. For both polymers, varying the steric bulk of the peripheral ethylene glycol (EG) units controlled the rates of self-assembly as well as the degrees of polymerization. This steric effect was further tunable, depending on the solvation state of the EG chains. Accordingly, this new family of supramolecular polymers was created by taking advantage of unique driving forces that depended on both the pH and solvent.